2021
DOI: 10.3390/cells10051004
|View full text |Cite
|
Sign up to set email alerts
|

Adipocyte, Immune Cells, and miRNA Crosstalk: A Novel Regulator of Metabolic Dysfunction and Obesity

Abstract: Obesity is characterized as a complex and multifactorial excess accretion of adipose tissue (AT) accompanied with alterations in the immune response that affects virtually all age and socioeconomic groups around the globe. The abnormal accumulation of AT leads to several metabolic diseases, including nonalcoholic fatty liver disorder (NAFLD), low-grade inflammation, type 2 diabetes mellitus (T2DM), cardiovascular disorders (CVDs), and cancer. AT is an endocrine organ composed of adipocytes and immune cells, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 162 publications
(140 reference statements)
1
33
0
1
Order By: Relevance
“…Research has identified vascular and bone cells as important actors in the homeostasis of the cardiovascular system, inflammation, immune system, energy balance, and mineral handling [1,2]. This is in line with other research areas, where complex interrelations between different organs and across organ systems are continuously being demonstrated [3][4][5][6][7][8].…”
Section: Introductionsupporting
confidence: 74%
“…Research has identified vascular and bone cells as important actors in the homeostasis of the cardiovascular system, inflammation, immune system, energy balance, and mineral handling [1,2]. This is in line with other research areas, where complex interrelations between different organs and across organ systems are continuously being demonstrated [3][4][5][6][7][8].…”
Section: Introductionsupporting
confidence: 74%
“…Thousands of mammalian mRNAs have been predicted to be targeted by miRNAs and hundreds of such interactions have been experimentally proven so far [ 20 , 21 ]. An overwhelming amount of data demonstrated that miRNAs fine-tuning of gene expression plays indispensable roles in human development and disease [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the host genes of circ-0003000 and circ-0139142 were ORC5 and NTRK2 we name them circORC5 and circNTRK2 respectively. We further validated the association between circNTRK2 and circNTRK2 expression and BMI, negative correlations of both circRNAs and BMI, indicating that downregulated obesity-associated ceRNA networks promoted obesity Discussion Accumulating evidence con rms that excessive energy storage in VAT leads to dysregulated secretion of adipokines and cytokines and state of chronic, low-grade in ammation and insulin resistance associated with obesity [18,19] . In this study, the VAT transcriptome revealed that DE genes and DE ncRNAs have an important role in the pathogenesis of obesity by modulating the process of in ammation and adipogenesis.…”
Section: Validation Of Obesity-related Ncrnas In the Cerna Networkmentioning
confidence: 66%